MCTS Microsoft® Exchange Server 2007 Configuration : Study Guide, Second Edition - Stidley, Joel (Sybex, 2009)
The most up-to-date study guide on Exam 70-236-written by Exchange MVP Joel Stidley Exam 70-236 has been updated to include the latest release of Exchange Server 2007: Service Pack 1 (SP1). This new edition is written by an Exchange MVP, author, trainer, and consultant who arms you with the most up-to-date information on preparing for Exam 70-236. You'll explore areas such as installing and configuring Microsoft Exchange Servers, configuring recipients and public folders, configuring Exchange infrastructure, monitoring and reporting, and configuring disaster recovery. Hands-on exercises, real-world scenarios, and challenging review questions are all aimed at helping you achieve your MCTS in Configuring Exchange Server 2007 by passing Exam 70-236. In-depth study guide, fully updated for Exchange Server 2007 Service Pack 1 Prepares you for taking Exam 70-236, which is a prerequisite for MCITP: Enterprise Messaging Administrator credential Includes hands-on exercises, real-world scenarios, and chapter review questions The CD-ROM features two practice exams, electronic flashcards, interactive chapter review questions, and the book in a searchable PDF This comprehensive study guide is the only one of its kind to walk you through Microsoft's MCTS: Exchange Server 2007 configuring exam. Note: CD-ROM/DVD and other supplementary materials are not included as part of eBook file.